Theories of social and spatial justice: dialogues with Geography beginning in the 1970s - Legroux, Jean [UNESP] (Universidade de São Paulo, 2022)
The debate around justice has been gaining ground in geography, especially beginning in the 1970s, with two seminal works, A theory of justice (Rawls, 1971) and Social justice and the city (Harvey, 1973). Beginning then, and without pretension of exhaustivity, we propose a journey through the discussions between several theories and principles of justice. As many processes analyzed in geography - such as segregation, marginalization, exclusion, and differentiation - expose injustices with a strong spatial expression, this reflection on justice offers theoretical and analytical tools for geographical analyses. In other words, we intend to establish the outlines of this discussion, to contribute to the understanding of the opening of geography to philosophical and ethics concerns. In that respect, we aim to present a wide vision of justice, around the tripod redistribution, recognition, and space, to finish with considerations about the concept of spatial justice.

El debate alrededor de la justicia ha ganado espacio en la geografía, especialmente a partir de los 1970s, con atención a A theory of justice (Rawls, 1971) y social justice and the city (Harvey, 1973). A partir de ahí, y sin pretensión a la exhaustividad, ese artículo pretende presentar un recorrido a través de los debates entre diversas teorías e/o principios de justicia. En la medida en que muchos procesos analizados en geografía - como la segregación, la marginalización, la diferenciación - revelan injusticias de expresión espacial, esta reflexión sobre la justicia ofrece herramientas teóricas pertinentes para los análisis geográficos. En otros términos, se establecen los contornos del debate, para contribuir a la comprensión de las implicaciones de la abertura de la geografía a preocupaciones filosófico-éticas. Así, se presenta una visión amplia de la justicia, articulada alrededor del trípode redistribución, reconocimiento y espacio, para finalmente hacer algunas consideraciones sobre el concepto de justicia espacial.
Las teorías de la justicia social y espacial: diálogos con la Geografía desde los años 1970
Keywords: Theory of justice; Spatial justice; Geography; Urban Studies